Investigation of a COVID-19 Outbreak and Its Successful Containment in a Long Term Care Facility in Qatar - Al Hamad, Hanadi; Malkawi, Manal Mustafa Mohd.; Al Ajmi, Jameela Ali A. A.; Al-Mutawa, Mariam Nooh J. H.; Doiphode, Sanjay Harish; Sathian, Brijesh (Frontiers in Public Health, 2021)
Introduction: The objective of this study is to investigate the COVID-19 outbreak and its successful containment in a long-term care facility, Qatar. Materials and Methods: It was a retrospective case series of 24 COVID-19 positive patients inclusive of elderly, patient attenders, and front-liners from 06th to 18th June 2020. Laboratory, radiological, and treatment findings were assessed from electronic records. Results: The outbreak management team concluded that despite all the pre-existing preventive measures implemented at the start of the pandemic, there was still evidence of lapses in infection control practices such as breach of infection control protocols like improper use of personal protective equipment. The infection prevention and control team promptly reassessed and implemented more stringent infection control methods and practices that successfully contained the outbreak on July 1, 2020. Among the seven elderly patients, the average age was 76.28 years±SD25.5 and all were females. 57% of the patients were symptomatic. The most common comorbidities were Dementia (57%), Diabetes mellitus (43%), Coronary Artery Disease (43%), and Seizures (43%). Ground glass appearances in the lungs were found in 29% of the patients. Among the three deceased patients, Dementia and Coronary Artery Disease were the common comorbidities. Persistent elevation in blood glucose levels was observed among all patients during this period of infection. Conclusion: Elderlies in long-term care facilities are with certain pre-existing comorbidities which makes them more prone to develop COVID-19 complications. Thus, intensive infection control measures like ongoing education and awareness, staff compliance monitoring, quick contact tracing, visitor policy revision, ongoing patient and caregivers monitoring are inevitable recommendations for effective outbreak prevention and management.